U.S. economic growth from 1976 - 1986: prospects, problems and patterns. volume 1 (Washington D.C. U.S. Government Printing Office, 1976)
This volume comprises two studies on the important subject of productivity. Both of these papers assess independently production trends over the next decade
Volume 1- productivity
osc 25/01/2019
Loans
Keywords: Economic Growth; U.S.A.